Household Asset Holding Diversification in Australia - Francesco Mariotti; Karen A. Mumford; Yolanda Pena-Boquete (Institute for the Study of Labor (IZA), 2014)
We explore asset holding diversification by Australian households, in particular, the household asset diversification participation decision (whether or not to diversify at all) is jointly estimated with the decision of how much to diversify. In so doing, recent literature on the modelling of proportions is combined with the growing body of research concerning household financial decision making. Our findings are consistent with the participation of households operating in diverse financial markets being constrained by ineffective information conduits, influencing the decision of whether or not to diversify. We further find that short term concerns over job security or health are associated with less participation in, as well as a lower extent of, asset holding diversification.
Keywords: J3; J7; 330; job insecurity; asset allocation; asset diversification; household finance; employment; Zero-Inflated Beta